United States : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
This paper discusses how financial innovation turned U.S. mortgages into an asset class with worldwide investor appeal. It suggests that U.S. financial markets have been skilful in developing tools that have helped households exploit favorable global financing conditions to boost home ownership and acquire housing wealth. It reviews trends in labor supply and demand, electricity sector challenges, oil price developments, and the performance of the U.S. economy. It analyzes U.S. banking developments, with focus on large complex banking groups (LCBGs), and describes the structural change and competition among auto manufacturers and airlines.